Representasi Tokoh Perempuan dalam Buku Teks Sejarah serta Pemahaman Siswa Kelas X SMK Hidayah Terhadap Peran Tokoh Perempuan dalam Sejarah - Gielda Latiffah Zahra; Syaiful Amin (Lembaga Teewan Journal Solutions, 2026)
History education plays a vital role in shaping students' understanding of past events and the figures involved in them. However, the representation of female figures in history textbooks remains limited. These representational constraints may influence students' perceptions regarding the contributions of women throughout history. This study aims to analyze the representation of women in history textbooks and assess the understanding of 10th-grade students. Data were collected through observations and interviews with teachers and students, as well as a documentary study of 10th-grade history textbooks published by Kemendikbudristek and Viva Pakarindo. The study concludes that a more in-depth and balanced presentation of female figures is necessary so that students' understanding of women's contributions to history can be more broadly developed.